Evaluation of integrated Child Development Services program in Gujarat, India for the years 2012 to 2015 - Rajesh K Chudasama; Umed V Patel; Amiruddin M Kadri; Arohi Mitra; Dhara Thakkar; Jasmin Oza (Wolters Kluwer Medknow Publications, 2016)
Background: The Integrated Child Development Services (ICDS) scheme has been operational for more than three decades in India. Objective: To evaluate the various aspects of the ICDS program in terms of inputs, process and outcome (coverage), utilization, and issues related to the ICDS program. Methods: A total of 130 Anganwadi centers (AWCs) were selected including 95 AWCs from rural areas and 35 AWCs from urban areas from April 2012 to March 2015, from 12 districts of Gujarat and the union territory of Diu. Information was collected for infrastructure, baseline characteristics of AWWs, provision, coverage and utilization of various ICDS services, and various issues related to program operation. Results: A majority of pregnant (94.7%) and lactating (74.4%) mothers, and adolescent girls (86.6%) were availing ICDS services. In 96.9% of the AWCs, a growth chart was available and 92.3% AWWs were using it accurately. A total of 14.9% children were underweight including 13.5% moderately and 1.4% severely malnourished children. Two-third (66.2%) children were covered by supplementary nutrition (SN). Only 14.6% of the AWCs reported 100% preschool education (PSE) coverage among children. More than half (55.4%) of the AWCs reported an interruption in supply during the last 6 months. Various issues were reported by AWWs related to the ICDS. Conclusion: The study has reported gaps in terms of infrastructure facility, different trainings, coverage, supply, and provision of SN, status of PSE activities in AWCs, and provision of different services to the beneficiaries.